Added value of seasonal hindcasts for UK hydrological drought outlook - Chan, Wilson C.H.; Arnell, Nigel W.; Darch, Geoff; Facer-Childs, Katie; Shepherd, Theodore G.; Tanguy, Maliko (European Geosciences Union, 2023)
The UK has experienced recurring periods of hydrological droughts in the past, including the latest drought declared in summer 2022. Seasonal hindcasts, consisting of a large sample of plausible weather sequences, can be used to add value to existing approaches to water resources planning. In this study, the drivers of winter rainfall in the Greater Anglia region are investigated using the ECMWF SEAS5 hindcast dataset, which includes 2850 plausible winters across 25 ensemble members and 3 lead times. Four winter clusters were defined using the hindcast winters based on possible combinations of various atmospheric circulation indices (such as North Atlantic Oscillation, East Atlantic Pattern and the El-Niño Southern Oscillation). Using the 2022 drought as a case study, we demonstrate how storylines of the event could be created in autumn 2022 to provide an outlook of drought conditions and to explore plausible worst cases over winter 2022/23 and beyond. The winter clusters span a range of temperature and rainfall response in the Anglian region and represent circulation storylines that could have happened over winter 2022/23. Although winter 2022/23 has now passed, we aim to demonstrate the added value of this approach to provide outlooks during an ongoing event with a brief retrospective of how winter 2022/23 transpired. Storylines created from the hindcast winters were simulated using the GR6J catchment hydrological model and the groundwater level model Aquimod at selected catchments and boreholes in the Anglian region. Results show that drier than average winters characterised by predominantly NAO-/EA- and NAO+/EA- circulation patterns would result in the continuation of the drought with a high likelihood of below normal to low river flows across all selected catchments and boreholes by spring and summer 2023. Catchments in Norfolk are particularly vulnerable to a dry summer in 2023 as river flows are not estimated to recover to normal levels even with wet La Niña winters characterised predominantly by NAO-/EA+ ...